Akibat Hukum Pemecahan Sertifikat Rumah Tanpa Adanya Penetapan Ahli Waris - Muhammad Rizki; Amiludin Amiludin; Erna Mastiningrum (Universitas Islam Darul Ulum, 2023)
Determination of heirs is to legally and fairly appoint heirs by authorized officials to be used in fulfilling administrative requirements relating to the affairs of heirs who have died and the affairs of heirs in the future. If there is a dispute over splitting the certificate without determining the heir, there will be consequences for the object of the dispute. This research explains and informs what legal consequences will arise if a legal action occurs, namely splitting a house certificate for a family that has not determined an heir. The research method uses normative research methods by examining the Decision of the Medan Religious Court Register Number: 172/pdt.P/2022/PA.Mdn by approaching statutory regulations and judges' decisions. The results of the research show that the legal consequences that will arise are conflicts between families if there is a transfer of certificate authority (sale and purchase transactions) and this can also relate to unlawful acts because there are parties who suffer losses from these legal acts, therefore the expert's determination Inheritance is mandatory to avoid conflicts between families.